2020
DOI: 10.21203/rs.3.rs-95141/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feed-forward, feed-back, and distributed feature representation during visual word recognition revealed by human intracranial neurophysiology

Abstract: Scientists debate where, when, and how different visual, orthographic, lexical, and semantic features are involved in visual word recognition. In this study, we investigate intracranial neurophysiology data from 151 patients engaged in reading single words. Using representational similarity analysis, we characterize the neural representation of a hierarchy of word features across the entire cerebral cortex. We find evidence of both feed-forward and feedback processing, with early representation of visual and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The finding of a second component is consistent with increasing evidence showing that visual word recognition is not limited to the left vOT. Instead, other higher-level linguistic representation areas also support final word recognition 13,14,63 . For example, a recent fMRI study showed that, connected with the middle and anterior vOT, other language areas (e.g., the supramarginal, angular gyrus, and inferior frontal gyrus) are responsible for lexical information processing especially for real words 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a second component is consistent with increasing evidence showing that visual word recognition is not limited to the left vOT. Instead, other higher-level linguistic representation areas also support final word recognition 13,14,63 . For example, a recent fMRI study showed that, connected with the middle and anterior vOT, other language areas (e.g., the supramarginal, angular gyrus, and inferior frontal gyrus) are responsible for lexical information processing especially for real words 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Finding of a second component is consistent with the increasing evidence showing that visual word recognition is not only limited to the left vOT. Instead, other higher-level linguistic representation areas also support final word recognition 13,14,62 . For example, a recent fMRI study showed that, connected with the middle and anterior vOT, other language areas (e.g., the supramarginal, angular gyrus, and inferior frontal gyrus) are responsible for lexical information processing especially for real words 13 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the sensitivity of neurons increases from familiar letter fragments and fragments combinations to more complex letter strings (e.g, bigrams and morphemes) and whole words. However, given the functional and structural connections between vOT (especially anterior regions) and other language areas mentioned above (i.e., AG, SMG, and STS), a considerable number of studies support the interactive theory in which feed-forward and feed-back processing mechanisms together contribute to final recognition of a word 5,6,45,62 . Specifically, the forward pathway conveys bottom-up progression from early visual cortex (e.g., visual area 4, V4) to vOT, which accumulates inputs about the elementary forms of words 73 , and continually from vOT to higher-level linguistic representation areas, which enable integration of orthographic stimuli with phonological and lexical representations 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Finding of a second component is consistent with the increasing evidence showing that visual word recognition is not only limited to the left vOT. Instead, other higher-level linguistic representation areas also support final word recognition (Long et al, 2020;Lerma-Usabiaga et al, 2018;Price & Devlin, 2011).…”
Section: Low-level Visual Processing Implicates Medial Occipital Areasmentioning
confidence: 99%
“…As a result, the sensitivity of neurons increases from familiar letter fragments and fragments combinations to more complex letter strings (e.g, bigrams and morphemes) and whole words. However, given the functional and structural connections between vOT (especially anterior regions) and other language areas mentioned above (i.e., AG, SMG, and STS), a considerable number of studies support the interactive theory in which feed-forward and feed-back processing mechanisms together contribute to final recognition of a word (Dehaene et al, 2005;Dehaene et al, 2015;Long et al, 2020). Specifically, the forward pathway conveys bottom-up progression from early visual cortex (e.g., visual area 4, V4) to vOT, which accumulates inputs about the elementary forms of words (Schurz et al, 2014), and continually from vOT to higher-level linguistic representation areas, which enable integration of orthographic stimuli with phonological and lexical representations (Price & Devlin, 2011).…”
Section: Low-level Visual Processing Implicates Medial Occipital Areasmentioning
confidence: 99%